Comparative Analysis of Earthquake Loss Estimation Using HAZUS Method with Modified Building Capacity Curve - Joesack Renaldi Sugianto; Cindrawaty Lesmana; Roi Milyardi (Universitas Tribhuwana Tunggadewi Malang, 2024)
Based on the World Bank publication in 2019, one of the strategies to improve disaster financial resilience is the availability of loss estimation data. As one of the vulnerable countries affected by earthquake disasters, Indonesia does not yet have a widely used pre-disaster estimation model. Model adoption is one of the strategies used to improve disaster resilience in Indonesia. The HAZUS method is a model FEMA (Federal Emergency Management Agency) developed to estimate earthquake losses in the US. The adoption process in Indonesia requires adjustments to the EDP (Engineering Demand Parameter) used in the HAZUS model. The EDP in the HAZUS model consists of capacity curves, fragility curves, and repair cost coefficients. The statistics of buildings affected by earthquakes in Indonesia from 2000 to 2020 show that residential houses are the most affected buildings. This study aims to obtain comparative results of the HAZUS model structural element loss estimation with modified data of local capacity curve pushover results in Indonesia. The study was conducted by performing a pushover analysis on a case study of a residential building to obtain a capacity curve. In this study, the EDP analyzed was only the EDP of the capacity curve. The case study was conducted at housing cluster X in West Bandung Regency, West Java, using house type T94/120 as the case study structure. The results of the capacity curve comparison show that the capacity curve of the local house from the pushover analysis has lower stiffness and ductility. The comparison of loss estimation for single hazard scenarios shows that the modified curve method has the most conservative loss estimation than HAZUS in the hazard of earthquake return periods of 100, 250, 500, and 750 years. The annual loss estimation shows that the modified capacity curve provides the most conservative or 37.5% larger in annual loss estimation. Â